The Spending Constraint Model for Market Equilibrium: Algorithmic, Existence and Uniqueness Results - Devanur, Nikhil; Vazirani, Vijay V. (In Proc. STOC 2004, 2004)
The traditional model of market equilibrium supports impressive existence results, including the celebrated Arrow Debreu Theorem. However, in this model, polynomial time algorithms for computing (or approximating) equilibria are known only for linear utility functions. We present a new, and natural, model of market equilibrium that not only admits existence and uniqueness results paralleling those for the traditional model but is also amenable to efficient algorithms.